Effects of play-way and guided-discovery instructional strategies on pupils' achievement in geometry in Akure south, Ondo state: a study in school effectiveness (2010)
School effectiveness is measured by the propotion of pupils in the school that can transit from one level of education to the other. Unfortunately, not all the pupils who registered in a cohort complete at the same time. This has implication on the methods adopted in such schoools. If the methods of teaching are not pupil centered, there is the likelihood that pupils may not perform well in school subjects especially in mathematics. Therefore, this study was designed to determine the effects of two teaching methods (play-way and guided discovery methods) in enhancing primary pupils' achievement in geometry. The pupils' gender was also taken to consideration in this study. The study adopted a 3x2 factorial design, the design incorporated treatment at three levels (two experimental and a control), gender at two levels (male and female). The sample is made up of two hundred and twenty-two (222), primary five pupils from six schools in Akure south LGA of Ondo state. Mathematics Achievement Test (MAT) was used to collect data. analysis of covariance (ANCOVA) was employed to test three null hypotheses. The study revealed that pupils taught with the play-way method and guided discovery method achieved significantly (p<.05) better than those taught with the conventional method. There is no significant difference between boys and girls' achievement in geometry. It is, therefore, recommended that practising teachers and teachers in training should adopt innovative teaching methods (play-way and guided discovery teaching methods) that are student-centered interactive in nature and gender friendly.